A Narrow-Linewidth Linearly Polarized 1018-nm Fiber Source for Pumping Diamond Raman Laser - Yang, Xuezong; Bai, Zhenxu; Jiang, Huawei; Mildren, Richard P.; Feng, Yan (Frontiers in Physics, 2021)
A 7.8 GHz linewidth ytterbium-doped fiber (YDF) laser with an output power of 75 W at 1018 nm is demonstrated based on narrow-bandwidth fiber Bragg gratings. Effective suppression of spectral broadening and amplified spontaneous emission is achieved by optimizing the resonator structure and active fiber parameters. An 1178 nm diamond Raman output pumped by this narrow-linewidth 1018 nm source is addressed in this study, which shows a promising application of generating sodium guide star laser at 589 nm. A single-longitudinal-mode Stokes with output power of 0.6 W is obtained using this multimode 1018 nm laser at the pump power of 13 W. The impact of pump spectral linewidth on the effective Raman gain coefficient is analyzed and the laser threshold of the diamond Stokes resonator increases with the broadening of the pump linewidth.